Optimizing library services via student internship community engagement at PEP Bandung - Rashel Dika Azzahra; Fatia Adhira Fauzi (Universitas Pendidikan Indonesia, 2025)
This program was implemented at the Politeknik Energi dan Pertambangan (PEP) Library as a form of student internship activities at the Indonesian University of Education. This program was motivated by the urgency of optimizing library services in higher education institutions, with a focus on the quality of collection development, collection organization, information services, and the use of information technology. In the digital era, through student internship programs implemented under the Merdeka Belajar Kampus Merdeka (MBKM) policy, universities are required to produce work-ready professionals. The purpose of this activity is to improve library service governance and to prepare prospective librarians to serve as managers. The steps taken in this program start from initial observation, mapping of institutional needs, implementing daily programs for 40 working days, and evaluating activities through seminars on results. The results obtained by students can contribute to circulation and reference services by entering collection data into SLiMS, performing classification and labeling, and providing user education. However, there are obstacles, including low user participation and limitations of the digital repository system. Efforts that can be implemented are service promotion, information literacy education, and improvements to the automation system. This activity demonstrates that student involvement in field practice can have a positive impact and was implemented effectively. Abstrak Program ini dilaksanakan di Perpustakaan Politeknik Energi dan Pertambangan (PEP) sebagai bentuk dari kegiatan magang mahasiswa Universitas Pendidikan Indonesia. Program ini dilatarbelakangi oleh urgensi pengoptimalisasian layanan perpustakaan di perguruan tinggi yang mengkaji kualitas pengembangan koleksi, pengorganisasian koleksi, pelayanan informasi dan pemanfaatan teknologi informasi yang dimana pada era digital melalui program magang mahasiswa sebagai implementasi kebijakan Merdeka Belajar Kampus Merdeka (MBKM) menuntut perguruan tinggi dapat mencetak professional yang siap kerja. Tujuan kegiatan ini adalah meningkatkan tata kelola layanan perpustakaan dan calon pustakawan sebagai pengelola. Langkah yang dilakukan pada program ini dimulai dari observasi awal, pemetaan pada kebutuhan institusi, pelaksanaan program harian selama 40 hari kerja dan evaluasi kegiatan melalui seminar hasil. Hasil yang didapatkan mahasiswa dapat berkontribusi dalam layanan sirkulasi dan referensi, input data koleksi ke SLiMS, klasiifikasi, pelabelan, dan edukasi pemustaka. Namun terdapat kendala seperti rendahnya partisipasi pemustaka serta keterbatasan sistem repository digital. Upaya yang dapat dilaksanakan adalah dengan promosi layanan, pengedukasian literasi informasi serta perbaikan sistem otomasi. Kegiatan ini telah menunjukkan adanya keterlibatan mahasiswa dalam praktik lapangan yang mampu memberi dampak positif dan telah tercapai dengan cukup optimal. Kata Kunci: layanan perpustakaan; otomasi perpustakaan; program magang mahasiswa; SLiMS